A practical generalized propensity score estimator for quantile continuous treatment effects - Alejo, Javier (2018)
A new Stata command, qcte, is proposed to implement several methods for estimation and inference for quantile treatment effects models with a continuous treatment. An easy semiparametric two-step estimator, where the first step is based on a flexible Box-Cox model is proposed as the default model of the command. Practical statistical inference procedures are developed using bootstrap. We implement some simulations exercises to show that the proposed methods have good performance. Finally, the command is applied to a survey of Massachusetts lottery winners to estimate the unconditional quantile effects of the prize amount, as a proxy of non-labor income changes, on subsequent labor earnings from U.S. Social Security records. The empirical results reveal strong heterogeneity across unconditional quantiles.